2020
DOI: 10.48084/etasr.3408
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Job ‎Scheduling with‎ Ions Motion Optimization Algorithm

Abstract: Cloud computing technology success comes from its manner of delivering information ‎technology services, how they are designed, propagated, maintained and scaled. Job Scheduling ‎on cloud computing is a crucial ‎research area and is known to be an NP-complete problem. Scheduling refers to assigning user requests to underlying resources effectively. ‎This paper proposes a new Job Scheduling mechanism for cloud computing ‎environment. The proposed mechanism is based on the Ions Motion Optimization (IMO) algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The selection process of genes based on natural methods revealed that simply the fittest kinds survive at the end of the process [17]. The research in [26] introduced the ions motion optimization (IMO) algorithm for IoT cloud job scheduling. The IMO mechanism includes two stages, namely the liquid and crystal phases, which work together to strike a balance between quick convergence and avoiding the local optima, thus enhancing the algorithm's performance [26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection process of genes based on natural methods revealed that simply the fittest kinds survive at the end of the process [17]. The research in [26] introduced the ions motion optimization (IMO) algorithm for IoT cloud job scheduling. The IMO mechanism includes two stages, namely the liquid and crystal phases, which work together to strike a balance between quick convergence and avoiding the local optima, thus enhancing the algorithm's performance [26].…”
Section: Related Workmentioning
confidence: 99%
“…The research in [26] introduced the ions motion optimization (IMO) algorithm for IoT cloud job scheduling. The IMO mechanism includes two stages, namely the liquid and crystal phases, which work together to strike a balance between quick convergence and avoiding the local optima, thus enhancing the algorithm's performance [26]. Job scheduling mechanisms for IoT cloud computing using optimization techniques based on shark smell optimization and chemical reaction optimization are introduced to enhance the job scheduling process [27,28].…”
Section: Related Workmentioning
confidence: 99%
“…The firefly mechanism was introduced to minimize the execution times. The study in [33] proposed an Ions Motion Optimization (IMO) algorithm for scheduling cloud jobs. The IMO mechanism consists of two phases, the liquid and the crystal phases.…”
Section: Related Workmentioning
confidence: 99%
“…The IMO mechanism consists of two phases, the liquid and the crystal phases. These phases maintain a balance between rapid convergence and avoiding local optima in the algorithm's performance [33].…”
Section: Related Workmentioning
confidence: 99%
“…For this reason, service controllers must use advanced and intelligent techniques to deploy large candidates of services. In recent years, several approaches for efficient service deployment have been proposed and are generally classified into 3 main categories [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]: (1) green IoT approaches [5][6][7][8][9], (2) optimization approaches [11][12][13][14], and (3) hybrid approaches combining mobile devices, fog, and cloud optimization techniques [15][16][17][18][19]. Authors in [8] presented a new model called Health-Fog based on deep learning for saving energy on the fog and the cloud while the data are processed and transmitted from the fog to the cloud.…”
Section: Introductionmentioning
confidence: 99%